2014
DOI: 10.1186/s12933-014-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin is a novel biomarker of acute coronary syndrome but not of stable angina pectoris

Abstract: BackgroundRecent evidence demonstrated that the circulating adipokines were associated with the onset of acute coronary syndrome (ACS) including unstable angina pectoris (UAP) and acute myocardial infarction (AMI). As a novel adipokine, chemerin has been related to atherosclerosis and the presence of coronary artery disease. However, the plasma levels of chemerin in patients with ACS have yet to be investigated.MethodsPlasma levels of chemerin and adiponectin were measured by an enzyme-linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 43 publications
(52 reference statements)
3
33
4
Order By: Relevance
“…A few studies showed that the reduced APN level was associated with severe coronary stenosis and high atherosclerotic burden . However, their findings were not confirmed in other studies . Similarly, no obvious correlation between the APN level and the severity of coronary lesions was seen in our research by measuring the Gensini score and the prevalence of multivessel disease.…”
Section: Discussioncontrasting
confidence: 94%
“…A few studies showed that the reduced APN level was associated with severe coronary stenosis and high atherosclerotic burden . However, their findings were not confirmed in other studies . Similarly, no obvious correlation between the APN level and the severity of coronary lesions was seen in our research by measuring the Gensini score and the prevalence of multivessel disease.…”
Section: Discussioncontrasting
confidence: 94%
“…Some studies showed positive association between chemerin levels and stable chronic coronary artery disease (CAD), but some found increased chemerin level only in patients with acute coronary syndrome and not in stable CAD (ref. 101 ). C-reactive protein (CRP) is an acute phase protein, produced in liver and adipose tissue.…”
Section: Adiponectinmentioning
confidence: 99%
“…One study showed that chemerin is associated with adipogenesis regulation and metabolic syndrome; the latter means the elevated body–mass index, and insulin resistance [9]. In addition, chemerin was found to be associated with impaired left ventricular systolic function, suggesting that chemerin is closely associated with ischemic heart disease, acute coronary syndrome, and heart failure [10, 11]. Chemokine like receptor 1 (CMKLR1), a G i protein-coupled chemerin receptor is highly expressed in vascular endothelial cells and is regulated by several proinflammatory cytokines, including tumor necrosis factor-alpha (TNF-alpha) and IL-6 [12].…”
Section: Introductionmentioning
confidence: 99%